The UK Experience of a Treatment Strategy for Pediatric Metastatic Medulloblastoma Comprising Intensive Induction Chemotherapy, Hyperfractionated Accelerated Radiotherapy and Response Directed High Dose Myeloablative Chemotherapy or Maintenance Chemotherapy (Milan Strategy). Issue 12 (14th August 2015) - Vivekanandan, Sindu; Breene, Richard; Ramanujachar, Ramya; Traunecker, Heidi; Pizer, Barry; Gaze, Mark N.; Saran, Frank; Thorp, Nicky; English, Martin; Wheeler, Kate AH; Michalski, Antony; Walker, David A.; et al.
<x xml:space="preserve">Abstract</x> Background Historically, the 5‐year overall survival (OS) for metastatic medulloblastoma (MMB) was less than 40%. The strategy of post‐operative induction chemotherapy (IC) followed by hyperfractionated accelerated radiotherapy (HART) and response directed high dose chemotherapy (HDC) was reported in a single center study to improve 5‐year OS to 73%. We report outcomes of this strategy in UK. Methods Questionnaires were sent to all 20 UK pediatric oncology primary treatment centers to collect retrospective data on delivered treatment, toxicity and survival with this strategy in children aged 3–19 years with MMB. Results Between February 2009 and October 2011, 34 patients fulfilled the entry criteria of the original study. The median age was 7 years (range 3–15). Median interval from surgery to HART was 109 versus 85 days in the original series. The incidence of grade 3 or 4 hematological toxicities with IC and HDC was 83–100%. All 16 patients who achieved complete response by the end of the regimen remain in remission but only three of 18 patients with lesser responses are still alive (P < 0.0001). With a median follow‐up of 45 months for survivors, the estimated 3‐year OS is 56% (95% CI 38, 71). This result is outside the 95% CI of the original study results and encompasses the historical survival result of 40%. Conclusion Within the limits of statistical significance, we did not replicate the improved survival results reported in the original series. The reasons include differences in patient sub‐groups and protocol administration. International randomized phase III studies are needed. Pediatr Blood Cancer 2015;9999:1–8 © 2015 Wiley Periodicals, Inc.